LEGAL PROTECTION OF COPYRIGHT FROM THE CRIME OF COMPUTER SOFTWARE PIRACY ACCORDING TO TRIPS AGREEMENT AND ITS IMPLEMENTATION IN INDONESIA - Riska Hanif Arma (Sean Institute, 2022)
Protection against computer software is often underestimated because it is considered not so important and there are no consequences, in fact piracy against computer software piracy is an unlawful act that results in criminal sanctions in the form of imprisonment and fines. As a result of rampant computer software piracy, Indonesia is faced with problems and bad impacts, both internationally and in Indonesia itself. Although in Indonesia it has been regulated in Law No. 28 of 2014 concerning Copyright, but there are no strict laws and regulations governing the act of software piracy. Where the purpose of this research is to find out and analyze the formulation of the problem. The legal research method that the author uses is normative, where the author examines library materials which are secondary data and is also called Library Legal Research, namely research on secondary data. The result of the research is that the regulation of copyright legal protection from software piracy crimes according to TRIPs is Law Number 28 of 2014 concerning Copyright which contains the ratification of the TRIPs agreement, then there is Law Number 11 of 2008 concerning Information and Electronic Transactions and Government Regulations. Republic of Indonesia Number 29 of 2004 concerning High-Tech Production Facilities for Optical Discs.